LEGAL FRAMEWORK OF HOUSE BUILDING IN ABANDONED HOUSING PROJECTS: THE LEGAL ISSUES IN MALAYSIA - Dahlan, Nuarrual Hilal Md (CENTRAL ASIA AND THE CAUCASUS, 2021)
Housing programme has been robustly implemented in Malaysia since Independence in 1957. At the commencement of the programme, the Federal Government provided housing accommodation to its citizens. However, due to the high demand for housing and that the Government was unable to provide adequate housing to the people, the Government invited the private sector to cooperate in supplying housing. Several laws have been enacted to control the housing industry that is initiated by the private sector. Among the laws are the Street, Drainage and Building Act 1974 (Act 133)('SDBA') and the Uniform Building By-Laws 1984 (G.N.5178/1984) ('UBBL'). Despite there are various housing policies and legislations to support housing programme, there are still many problems arising from the implementation of housing programmes in Malaysia. An example of the problems is the abandoned housing projects. Since the 1970s until to date, this issue is still occurring in Malaysia. Many public purchasers have become aggrieved in abandoned housing projects, suffered damage and losses. This paper aims to highlight the problems of abandoned housing projects through the analysis of building laws in Malaysia. This paper used qualitative case study and legal research methodologies to analyse the issues and to meet the research objectives. Through this paper, it is evident that there are weaknesses in the building laws. Hence, appropriate amendments and improvement of the laws should be made to empower the laws and provide adequate measures against the issues. The results of this paper will provide new ideas to housing practitioners and policymakers in dealing with the problems of abandoned housing projects in Malaysia towards achieving the 12th Malaysia Plan and the Sustainable Development Goals (SDGs).